Direct X-Ray Detection of the Spin Hall Effect in CuBi - Sandra Ruiz-Gómez; Rubén Guerrero; Muhammad W. Khaliq; Claudia Fernández-González; Jordi Prat; Andrés Valera; Simone Finizio; Paolo Perna; Julio Camarero; Lucas Pérez; Lucía Aballe; Michael Foerster (Physical Review X, 2022)
The spin Hall effect and the inverse spin Hall effect are important spin-charge conversion mechanisms. The direct spin Hall effect induces a surface spin accumulation from a transverse charge current due to spin-orbit coupling even in nonmagnetic conductors. However, most detection schemes involve additional interfaces, leading to large scattering in reported data. Here we perform interface-free x-ray spectroscopy measurements at the Cu L_{3,2} absorption edges of highly Bi-doped Cu (Cu_{95}Bi_{5}). The detected x-ray magnetic circular dichroism signal corresponds to an induced magnetic moment of (2.2±0.5)×10^{−12}  μ_{B} A^{−1} cm^{2} per Cu atom averaged over the probing depth, which is of the same order of magnitude as found for Pt measured by magneto-optics. The results highlight the importance of interface-free measurements to assess material parameters and the potential of CuBi for spin-charge conversion applications.